Digital infrastructure and intra-provincial balanced development: Evidence from China’s provincial panel data - Shuping Lin; Lingling Zuo; Tao Cen (PLoS ONE, 2025)
Unbalanced regional development poses a significant challenge to global economic growth. While existing studies have primarily concentrated on disparities between provinces, there is a notable lack of research addressing regional imbalances within a single province. In this paper, we use urban-level indicators to assess the level of intra-provincial regional balanced development in China. Based on provincial panel data from 2013 to 2022, we examine the impact of digital infrastructure on balanced regional development. We find that digital infrastructure significantly promotes balanced regional development using a fixed-effect regression model. This conclusion still holds after a series of robustness tests including instrumental variables, considering variable lag effects. Then we identify technological innovation and industrial structure upgrading as the primary mechanisms driving this relationship. Heterogeneity analysis reveals that the impact of digital infrastructure on balanced provincial development is more pronounced in regions with higher levels of urbanization, whereas the heterogeneity associated with financial development levels is statistically insignificant. Based on these findings, the paper offers policy recommendations aimed at leveraging digital infrastructure to further empower balanced development across provinces.